Intracranial subarachnoid hemorrhage caused by an aneurysm at the thoracic spinal region: case report and literature review. (1st November 2020) - Yokosuka, Junichi; Fukaya, Shunsuke; Yamomoto, Shinji; Ueki, Keisuke; Kim, Phyo
Abstract: Background: The most common cause of intracranial subarachnoid hemorrhage (SAH) is an intracranial aneurysm or other vascular lesion; however, spinal lesions have also been implicated. Furthermore, vascular lesions rarely occur in the thoracolumbar region. We herein presented a case of intracranial SAH caused by an isolated aneurysm in the thoracic spinal artery. Case presentation: A 79-year-old woman developed the sudden onset of headaches in the parietal and occipital regions followed by vomiting. Head computed tomography (CT) scans showed SAH in the basal cistern and around the parietal lobe cortex. Cerebral angiography detected no aneurysm or vascular malformation. Spinal CT on day 1 showed extensive SAH at the posterior surface of the spinal cord, which was the most prominent at the level of T9/10, and spinal angiography subsequently revealed an aneurysm fed by the T10 radicular artery. The aneurysm was resected by T8-10 laminectomy, and the patient recovered with no long-term neurological deficit. Conclusions: A literature review revealed 17 cases of intracranial SAH from thoracolumbar vascular lesions. Most cases resulted in poor functional outcomes, which occurred in the later phase of the disease and may have been avoided with earlier diagnoses and interventions. We suggest whole spine CT as a useful tool for rapid screening of this rare lesion, and is recommended when an initial survey for intracranial lesions does not detect any likely lesions. Furthermore, ventricular reflux on head CT may lead to an accurate diagnosis in the absence of spinal symptoms.